2014
DOI: 10.1634/theoncologist.2013-0335
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib of Sorafenib in Combination With Everolimus in Patients With Advanced Solid Tumors, Selected on the Basis of Molecular Targets

Abstract: Background. Molecular alterations of the PI3K and Ras pathways often occur in human cancer. In this trial, the pharmacokinetics, toxicity, and activity of two drugs inhibiting these pathways-everolimus and sorafenib-were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Multi-kinase inhibitors targeting mainly FLT3 are generally accepted for acute myeloid leukemia (AML) treatment but are not clinically used on solid tumors due to low efficacy. Currently, combination treatments, instead of single therapeutic agents, are being extensively investigated for the treatment of solid tumors [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-kinase inhibitors targeting mainly FLT3 are generally accepted for acute myeloid leukemia (AML) treatment but are not clinically used on solid tumors due to low efficacy. Currently, combination treatments, instead of single therapeutic agents, are being extensively investigated for the treatment of solid tumors [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hypophosphataemia occurs frequently with everolimus [Toffalorio et al 2014] and has also been reported for HDAC, MEK and ALK inhibitors. Dr Roila believes that periodic monitoring is recommended with phosphate supplementation and drug interruption need only occur in severe cases.…”
Section: Endocrine Toxicitymentioning
confidence: 99%
“…Although bryostatin-1 development has been halted, studies such as this must be published to inform the future development of other protein kinase C inhibitors. Exhibit C is a combination of sorafenib with everolimus selected on the basis of molecular targets [4]; the reader can decide, is this progress or are we running in place?…”
mentioning
confidence: 99%